FRI0302 Systemic lupus erythematosus-associated thrombotic microangiopathies in 60 patients: clinical features, prognosis and treatment in a french multicentric cohort. (12th June 2018) - Couture, P.; Hié, M.; Pineton de Chambrun, M.; Galicier, L.; Costedoat-Chalumeau, N.; Deroux, A.; Kanouni, T.; Roumier, M.; Melki, I.; Mathian, A.; Coppo, P.; Amoura, Z.
Abstract : Background: The occurrence of a TMA during SLE is a rare event that complicates 1% to 4% of lupus. The full spectrum of TMA can be encountered in the course of SLE: acquired thrombotic thrombocytopenic purpura (PTT), TMA associated with glomerulonephritis (TMA GN), atypical hemolytic uremic syndrome (aHUS), microangiopathic antiphospholipid syndrome (MAPS; defined or probable catastrophic antiphospholipid syndrome) or HELLP syndrome during pregnancy. Objectives: To describe the clinical phenotype of TMA in lupus, to specify the prognosis and to identify factors allowing early classification and management of the different subtypes. Methods: We performed a French multicentric retrospective study from January 1987 to December 2017 in units of internal medicine, nephrology and ICU. Inclusion criteria associated SLE defined by the ACR and/or SLICC criteria and a TMA defined either by the presence of microangiopathic anaemia and peripheral thrombocytopenia, either by histological signs of TMA. Results: 68 events of TMA occurred in 60 SLE patients; median age was 24 years; 56 women (F/M ratio: 14). Diagnosis of SLE was assessed at a paediatric age in 24 (35.8%) patients. Clinical manifestations of SLE were: acute cutaneous lupus (n=48, 71%), arthritis (n=36, 53%), pleuritis (n=13, 19%), pericarditis (n=25, 37%), renal involvement (n=39, 57% including 20 class IV glomerulonephritis) and auto-immune cytopenia (n=22, 32%). Triggering factors of TMA were: lupus flare (n=38), infections (n=12), pregnancy and peripartum (n=3), or therapeutic rupture (n=4). Clinical and biological features at diagnosis of each subtypes of TMA are presented in table 1. A platelet count lower than 28 000/mm3 was predictive of TTP diagnosis (Se=90, 5%, Sp=88, 5%), likewise a creatinine plasma level greater than 100 µmol/L was predictive of TMA GN (Se=88, 5%, Sp=85%). The treatment of TMA included (alone or in combination): corticosteroids in all cases, plasma exchange (n=52), cyclophosphamide (n=28), Rituximab (n=15), Eculizumab (n=2), antiplatelet agent (n=36), and/or effective anticoagulation (n=26). The median duration of follow-up was 150 months. Among TMA GN patients, the final median GFR was 58 mL/min (range: 0–120) with 5 individuals on chronic dialysis and 1 kidney transplant. Among TTP patients, one died from TMA, whereas the final median GFR of survivors (n=59) was 97 mL/min (range: 64–150), without any patient requiring dialysis. Table 1 Comparisons of clinical and laboratory data in different subtypes of TMA in SLE Conclusions: SLE-associated TMA is a heterogeneous syndrome. TTP with a decreased ADAMTS13 activity and a low platelets level (<28000/mm 3 ) have a good renal prognosis, whereas TMA GN with a high creatinine level (>100 µmol/L) have a poor renal prognosis. Early subtypes classification is mandatory for the clinician to provide prompt and appropriate management of this life-threatening complication. Disclosure of Interest: None declared